2020
DOI: 10.3390/jcm9072130
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in PARP1 Targeted Nuclear Imaging and Theranostic Probes

Abstract: The central paradigm of novel therapeutic approaches in cancer therapy is identifying and targeting molecular biomarkers. One such target is the nuclear DNA repair enzyme Poly-(ADP ribose) polymerase 1 (PARP1). Sensitivity to PARP inhibition in certain cancers such as gBRCAmut breast and ovarian cancers has led to its exploitation as a target. The overexpression of PARP1 in several types of cancer further evoked interest in its use as an imaging target. While PARP1-targeted inhibitors have fast develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…It was also found that MnP inhibits the antiapoptotic proteins, bcl-2 and mcl-1, which are overexpressed in high-grade serous cancer cells [129], thus promoting apoptotic pathways (see Figure 2). PARP is also overexpressed in several types of ovarian cancer cells, and MnP was found to suppress its activity via increasing levels of inactive cleaved PARP ( Figure 2) [137]. MnP was also found to increase the levels of activated, cleaved caspase 3 [137].…”
Section: Ascorbate Enhances the Anticancer Radioand Chemosensitizing mentioning
confidence: 96%
See 1 more Smart Citation
“…It was also found that MnP inhibits the antiapoptotic proteins, bcl-2 and mcl-1, which are overexpressed in high-grade serous cancer cells [129], thus promoting apoptotic pathways (see Figure 2). PARP is also overexpressed in several types of ovarian cancer cells, and MnP was found to suppress its activity via increasing levels of inactive cleaved PARP ( Figure 2) [137]. MnP was also found to increase the levels of activated, cleaved caspase 3 [137].…”
Section: Ascorbate Enhances the Anticancer Radioand Chemosensitizing mentioning
confidence: 96%
“…PARP is also overexpressed in several types of ovarian cancer cells, and MnP was found to suppress its activity via increasing levels of inactive cleaved PARP ( Figure 2) [137]. MnP was also found to increase the levels of activated, cleaved caspase 3 [137]. TP53 and MAPK/ERK are mutated in low-grade serous cancer [127] allowing for the therapeutic interventions with their inhibitors, MnPs prospectively being one of those.…”
Section: Ascorbate Enhances the Anticancer Radioand Chemosensitizing mentioning
confidence: 99%
“…In disease settings, extensive DNA damage can trigger PARP-1 hyperactivation, leading to redox imbalances and excess accumulation of the highly branched anionic poly(adenosine diphosphate-ribose) polymer, all of which promote the dysregulation of critical cell processes (4). Although moderate genotoxic stimuli facilitate PARP-1 activation and DNA repair, increased PARP-1 activity and expression have been linked to several pathologic states, with the most prominent being the overexpression of PARP-1 across a diverse set of carcinomas ( 5)-an observation that has led to recognition of PARP-1 as an attractive imaging target in human malignancies (5). PARP-1 is also involved in modulating cancer cell immunogenicity and has been implicated in the regulation of inflammatory response mechanisms, including the modulation of disease-associated genes such as chemokines, proinflammatory mediators, and metabolic factors (6).…”
Section: The Role Of Parp-1 In Dna Repair and Diseasementioning
confidence: 99%
“…While PARP-1 targeted inhibitors have been relatively fast developed and approved, the determination of PARP-1 expression might help to predict the response to PARP inhibitor treatment. Sankaranarayanan et al summarize the recent preclinical advancements in imaging and theranostic PARP-1 targeted tracers [ 92 ]. To estimate PARP1 levels, several imaging probes with fluorescent or gamma/beta-emitting radionuclides have been proposed.…”
Section: Theranostic Pet Tracersmentioning
confidence: 99%